Current Hepatitis B Reports - Keeffe, Emmet B.; SpringerLink (Online service) (New York : Current Medicine Group LLC : Imprint: .)
The aim of this journal is to help the reader, by providing in a systematic manner, the views of experts on the current advances in the hepatitis B field in a clear and readable form and by providing reviews which highlight the most important papers recently published from the wealth of original publications. We accomplish this aim by appointing major authorities in four major subject areas across the discipline to select topics to be reviewed by leading experts who can emphasize recent developments and highlight important papers published over the last year on their topics. We also provide the reader with valuable web sites from well-known figures in the field.
Keywords: Medicine; Internal medicine; Hepatology; Hepatology; Internal Medicine; Medicine/Public Health, general